2022
DOI: 10.25159/2520-5293/8888
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance the Resilience of Nurse Managers

Abstract: Nurse managers are often exposed to workplace stressors, thus it becomes necessary to enhance their resilience which will enable them to withstand workplace adversity. The purpose of the current study was to develop strategies that can enhance the resilience of nurse managers. A purposive sample of 49 nurse managers working in the general wards of 11 public hospitals in Botswana was undertaken. The study was done in two phases. Phase 1 of the study entailed the empirical phase that followed a concurrent mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Scholars studying resilience among healthcare professionals and military recruits contextualize their studies as investigating resilience in high-stress occupations. Boitshwarelo et al (2020) used a mixed method design to study nurse managers; individuals with moderate to high resilience scores as measured by the Wagnild and Young Resilience Scale were then studied qualitatively. The study found that resilient nurse managers could: (a) uphold personal values, (b) employ life skills, (c) apply appropriate leadership skills, and (d) access social support (Boitshwarelo et al, 2020).…”
Section: Leadership and Resilience In Successful Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars studying resilience among healthcare professionals and military recruits contextualize their studies as investigating resilience in high-stress occupations. Boitshwarelo et al (2020) used a mixed method design to study nurse managers; individuals with moderate to high resilience scores as measured by the Wagnild and Young Resilience Scale were then studied qualitatively. The study found that resilient nurse managers could: (a) uphold personal values, (b) employ life skills, (c) apply appropriate leadership skills, and (d) access social support (Boitshwarelo et al, 2020).…”
Section: Leadership and Resilience In Successful Individualsmentioning
confidence: 99%
“…Boitshwarelo et al (2020) used a mixed method design to study nurse managers; individuals with moderate to high resilience scores as measured by the Wagnild and Young Resilience Scale were then studied qualitatively. The study found that resilient nurse managers could: (a) uphold personal values, (b) employ life skills, (c) apply appropriate leadership skills, and (d) access social support (Boitshwarelo et al, 2020). Ledford et al (2021) investigated the differences between resilience, hardiness, and grit among elite military personnel and developed a new, more parsimonious measure of resilience than the Connor-Davidson Resilience Scale.…”
Section: Leadership and Resilience In Successful Individualsmentioning
confidence: 99%
“…Interestingly, the unit manager's key role is to lead his or her subordinates in his or her perspective unit [17]. Therefore, a unit manager must be in possession of leadership skills, communication skills, and resilience in order to guide the team in the right direction [18]. Unit managers must be able to manage conflict situations and ensure team cohesion [19].…”
Section: Introductionmentioning
confidence: 99%
“…The power of positive psychology is its ability to apply the most successful aspects of individuals to their unique situations. With this in mind, recent advances in positive psychology have advanced studies on building resilience and promoting positive psychological functioning (Didkowsky and Ungar, 2016;Sandberg and Grant, 2017;Dubus, 2018;Gonzalez-Mendez et al, 2021;Boitshwarelo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%